1987
DOI: 10.1093/oxfordjournals.humrep.a136554
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and serum binding of Ru 486 in women after various single doses*

Abstract: The metabolism of RU 486 was studied in female volunteers following a single oral administration of 100, 400, 600 or 800 mg of RU 486. The serum concentrations of RU 486 were generally not affected by the dose within the range examined and they stayed at micromolar concentrations during the 48 h studied. RU 486 was metabolized extensively in a dose-dependent manner by two-step demethylation, and by hydroxylation. Serum levels of the monodemethylated metabolite always exceeded those of RU 486. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…Single dose studies have suggested that in human serum RU-486 is bound to ac-l-acid glycoprotein and the plasma concentration may be limited by the saturation of this protein (2,18). On the other hand, onapristone does not appear to bind to this protein (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single dose studies have suggested that in human serum RU-486 is bound to ac-l-acid glycoprotein and the plasma concentration may be limited by the saturation of this protein (2,18). On the other hand, onapristone does not appear to bind to this protein (1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite considerable progress in the understanding of the biochemistry and molecular biology of steroid hormone receptors and the interaction of antiprogestins with the receptor (1, 2, 14-17), very little is known about the potential nonhormonal actions of these compounds. It is efficiently absorbed from the intestine and plasma concentrations reach micromolar amounts (1,2,18,19). We anticipated that RU-486 may interact with an oxidation system and may exhibit potent antioxidant properties, based on its chemical nature, its similarity to the antioxidant, Lazaroid U-74,500A (a lipophilic dimethyl-or ethyl-amino group), and the formation of mono-and di-demethylated and hydroxylated metabolic products (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The N-monodemethylated product is the primary metabolite, and after oral administration of 100-800 mg mifepristone, its concentration exceeds that of the parent compound [21,22]. At higher dose levels of mifepristone (>400 mg), the other metabolites also accumulate at high concentrations [21]. Both the demethylated and hydroxylated metabolites are eventually further degraded and excreted into bile [11].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The adverse effects observed after use of mifepristone are mainly gastrointestinal, including nausea, vomiting, abdominal pain and skin rashes. 30 Introduction of Misoprostol in late 70's revolutionised the management of termination of pregnancy. It is known that prostaglandins stimulate uterine contractility at any stage of pregnancy and also cause cervical ripening and dilatation.…”
Section: Discussionmentioning
confidence: 99%